Observation of a Possible New Isomer in 175Ir - 王华磊 宋立涛 赵维娟 刘忠侠 张玉虎 周小红 郭应祥 雷祥国 (Chinese physics letters, 2010)
The neutron deficient nuclide 175Ir was produced by irradiation of 146Nd with 210 MeV 35Cl via a fusion-evaporation reaction channel. The reaction products were transported to a low-background location using a helium-jet recoil fast-moving tape-transport system for measurement. The experimental devices and data analysis method are introduced. Based on the decay-curve fitting of the β-delayed γ ray from 175Ir, realized by the least-square method, a new long-lived isomeric state of 175Ir is proposed and briefly discussed.